2011
DOI: 10.26512/ser_social.v13i28.12682
|View full text |Cite
|
Sign up to set email alerts
|

A Política Social do Governo Lula (2003-2010):

Abstract: O objetivo desse ensaio é analisar a política social do governo do presidente Luis Inácio "Lula" da Silva (2003-2010) na perspectiva da trajetória da proteção social brasileira nas últimas cinco décadas. Argumenta-se que ela se insere numa longa fase de tensões entre paradigmas (Estado Mínimo versus Estado de Bem-Estar Social) observadas no período entre 1990 e 2002. Essas fricções, intensas nessa quadra, permaneceram vivas entre 2003 e 2005 e arrefeceram entre 2006 e 2010. Mais especificamente, inserida nessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 3 publications
0
11
0
16
Order By: Relevance
“…According to Marques and Mendes (2007), the first government of President Lula da Silva (2003Silva ( -2006 was marked by an economic policy that favored agribusiness and national and international financial capital, maintaining a high return on capital and high-interest rates. Due to the economic situation of high inflation rates, measures such as public primary surplus, and the restriction on public spending stood out in this period (Fagnani, 2011). Marques and Mendes (2007) observed that, at the same time, the government implemented several policies aimed at the poorest part of the Brazilian population.…”
Section: The Social and Political Context Of Brazilian Vocational Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Marques and Mendes (2007), the first government of President Lula da Silva (2003Silva ( -2006 was marked by an economic policy that favored agribusiness and national and international financial capital, maintaining a high return on capital and high-interest rates. Due to the economic situation of high inflation rates, measures such as public primary surplus, and the restriction on public spending stood out in this period (Fagnani, 2011). Marques and Mendes (2007) observed that, at the same time, the government implemented several policies aimed at the poorest part of the Brazilian population.…”
Section: The Social and Political Context Of Brazilian Vocational Educationmentioning
confidence: 99%
“…Marques and Mendes (2007) observed that, at the same time, the government implemented several policies aimed at the poorest part of the Brazilian population. According to Fagnani (2011), the early years of President Lula da Silva's administration was marked by the debate regarding the directions of the social strategy, highlighting the dispute between "focusing" and "universalization," opening space also to elements of the liberal agenda in the social field. Fagnani (2011) explains that from 2003, various mechanisms of pressure and social accountability were implemented, such as national conferences in the area of health, education, social security, urban policy, and policies for women.…”
Section: The Social and Political Context Of Brazilian Vocational Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2000s, arguments justifying fiscal adjustment continued to constitute the core of the federal government's official communications on social security. The threat of cuts was ever-present, along with the realization of other measures that had been secondary for the previous government (Fagnani, 2011). In addition to the limits on social spending, the fiscal adjustment regime subjected social security to the systematic reduction of its constitutionally established financing through the mechanism called the "unbundling of Union revenues," which emerged with the Real Plan in 1994 and was later made law.…”
Section: Tax Adjustments and The Deconstruction Of Social Security Rimentioning
confidence: 99%
“…The struggle for redemocratization in Brazil was an important milestone on this path, since it disseminated a new social agenda founded on the principles of social security. In this sense, the formal definition of social rights of the 1988 Constitution suggested the structuring of policies inspired by the values of the postwar European welfare state-a concept of social security as a public right guaranteed by the state to all citizens, with the possibility of its acting as a mechanism for the redistribution of income (Fagnani, 2011).…”
mentioning
confidence: 99%